2013
DOI: 10.3109/09638288.2012.748841
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation in physical therapy: from theory to practice

Abstract: In order to support EBP, knowledge translation interventions can be used to support best practice. Implementation of new knowledge should be guided by a framework or a conceptual model. Consensus on the evidence must be reached and assessment of context-related factors should be done prior to the implementation of any KT intervention. Intervention strategies should be active, multi-component and include individuals with intermediary positions that can facilitate the KT process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 51 publications
0
59
0
1
Order By: Relevance
“…In some instances, patients treated by physical therapists (PTs) receive insufficient, ineffective or potentially harmful treatment despite available scientific evidence that supports other clinical approaches 4 . Knowledge translation (KT) 5 interventions * have been proposed as a key means to promote the uptake of research evidence into clinical practice and thus contribute to improved care for patients treated by PTs 6,7 . Despite this recognition of their importance, there remains debate and uncertainty regarding the best ways to design and implement KT interventions in healthcare, including PT 8 .…”
Section: Body Of the Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, patients treated by physical therapists (PTs) receive insufficient, ineffective or potentially harmful treatment despite available scientific evidence that supports other clinical approaches 4 . Knowledge translation (KT) 5 interventions * have been proposed as a key means to promote the uptake of research evidence into clinical practice and thus contribute to improved care for patients treated by PTs 6,7 . Despite this recognition of their importance, there remains debate and uncertainty regarding the best ways to design and implement KT interventions in healthcare, including PT 8 .…”
Section: Body Of the Manuscriptmentioning
confidence: 99%
“…Similarly, they can support researchers and clinicians to identify specific facilitators, and select strategies to enhance them. Highlighting these impacts, several authors have advanced the view that KT activities related to rehabilitation and disability would benefit from increased use of conceptual frameworks 7,23 . Despite the development of many KT frameworks over the past two decades, their uptake across healthcare disciplines, including PT, remains limited 8 .…”
Section: The Contributions Of Conceptual Framework In Pt Kt Intervenmentioning
confidence: 99%
“…However, the physiotherapist's own beliefs and pain coping strategies are known to influence decision-making and management in low back pain [165][166][167][168]. Larger treatment effects may have been observed if specialist musculoskeletal physiotherapists were involved in the study, or, if physiotherapists had been recruited based on their specific interest in neck rehabilitation and had received a more extended education as part of a planned implementation strategy [169]. On the other hand, this may have reduced the generalizability of the results.…”
Section: Evaluation Of Spt Compared To Sa In Patients With Cr (Paper mentioning
confidence: 99%
“…5,10 CoPs are defined as a group of people who share a concern and interact regularly to learn how to improve something they do.11 Crucial characteristics of effective CoPs include a "domain of interest," a "community" that shares an interest, and a "practice. "11 CoPs are reported to ease knowledge management and learning, and foster sharing of tacit knowledge.9 CoPs can contribute to improving health care measured through cost savings, increased professional competencies, the reduction of geographical and organizational barriers and professional isolation, and the implementation of new processes and technologies.9,12 Virtual methods seem to be effective in supporting CoP knowledge sharing and communication among CoP members, notably through the use of virtual forums and electronic sharing of resources.9,12 http://ovidsp.tx.ovid.com.ezproxy.usherbrooke.ca/sp-3.21.1b/ovidweb.cgi Virtual CoPs (vCoPs) are comprised of three groups: the core, the active, and the peripheral members.13 Most members are peripheral, rarely participating actively, but gaining insight from reading discussions, whereas active members participate occasionally in the CoP but not to the extent of the core group.13 A common model in health care is to have a core group composed of a coordinator and clinical leaders, who act as facilitators, have content and resource expertise, and enable social processes (eg, create an engaging climate).14 Some evidence suggests that a face-to-face meeting of the vCoP members can be important before meeting through virtual methods, whereas other studies have demonstrated that groups, who met solely or largely in virtual environments, can also function quite effectively.…”
mentioning
confidence: 99%